Horizontal Divestiture: highlights of a conference on whether oil companies should be prohibited from owning nonpetroleum energy resources, held in Washington, D.C. on 27 January 1977 - Moore, W. S.; American Enterprise Institute for Public Policy Research (Washington: American Enterprise Institute for Public Policy Research, 1977)
This booklet presents a brief edited version of the highlights of the Conference on Horizontal Divestiture in the Oil Industry, held in Washington, D.C., on 27 January 1977, under the sponsorship of the American Enterprise Institute for Public Policy Research. The purpose of this conference is to bring together persons with expertise and interest in this and similar questions from the academic world, government, business, and the public to exchange their views and thereby aid in the examination of horizontal divestiture and related issues.
Includes bibliographical references.
ne 16/04/2018
Loan
Keywords: Petroleum Industry and Trade; Corporate Divestiture